Rejuvenation of Neutrophil Functions in Association With Reduced Diabetes Risk Following Ten Weeks of Low-Volume High Intensity Interval Walking in Older Adults With Prediabetes – A Pilot Study - David B. Bartlett; David B. Bartlett; David B. Bartlett; Cris A. Slentz; Leslie H. Willis; Andrew Hoselton; Janet L. Huebner; Virginia B. Kraus; Jennifer Moss; Michael J. Muehlbauer; Guillaume Spielmann; Deborah M. Muoio; et al. (Frontiers in Immunology, 2020)
Neutrophil dysfunction is a common feature of aging, and is associated with the pathogenesis of many age-related diseases, including type 2 diabetes mellitus (T2DM). Although exercise training improves metabolic health, decreases risk of T2DM, and is associated with improving neutrophil functions, involvement in regular physical activity declines with age. The aim of this study was to determine if neutrophil functions could be improved in association with changes in fitness and metabolic parameters in older adults at risk for T2DM using 10-weeks of low volume high-intensity interval exercise training (HIIT). Ten older (71 ± 5 years) sedentary adults with prediabetes (HbA1c: 6.1 ± 0.3%) completed 10 weeks of a supervised HIIT program. Three 30 min sessions/week consisted of ten 60 s intervals of low intensity [50–60% heart rate reserve (HRR)] separated with similar durations of high intensity intervals (80–90% HRR). Before and after training, glucose and insulin sensitivity, neutrophil chemotaxis, bacterial phagocytosis, reactive oxygen species (ROS) production, and mitochondrial functions were assessed. Exercise-mediated changes in cardiorespiratory fitness (VO2peak) and neutrophil functions were compared to six young (23 ± 1 years) healthy adults. Following training, significant reductions in fasting glucose and insulin were accompanied by improved glucose control and insulin sensitivity (all p < 0.05). Before exercise training, VO2peak in the old participants was significantly less than that of the young controls (p < 0.001), but increased by 16 ± 11% following training (p = 0.002) resulting in a 6% improvement of the deficit. Neutrophil chemotaxis, phagocytosis and stimulated ROS production were significantly less than that of the young controls, while basal ROS were higher before training (all p < 0.05). Following training, chemotaxis, phagocytosis and stimulated ROS increased while basal ROS decreased, similar to levels observed in the young controls (all p < 0.05) and reducing the deficit of the young controls between 2 and 154%. In five of the adults with prediabetes, neutrophil mitochondrial functions were significantly poorer than the six young controls before training. Following training, mitochondrial functions improved toward those observed in young controls (all p < 0.05), reducing the deficit of the young controls between 14.3 and 451%. Ten weeks of HIIT in older adults at risk for T2DM reduced disease risk accompanied by improved primary and bioenergetic neutrophil functions. Our results are consistent with a reduced risk of infections mediated by relationships in exercise induced systemic and cellular metabolic features.Clinical Trial Registration:www.ClinicalTrials.gov, identifier NCT02441205, registered on May 12th, 2015.